Comprehensive evaluation of the flavonol anti-oxidants, alpha-glycosyl isoquercitrin and isoquercitrin, for genotoxic potential. (March 2018) - Hobbs, Cheryl A.; Koyanagi, Mihoko; Swartz, Carol; Davis, Jeffrey; Kasamoto, Sawako; Maronpot, Robert; Recio, Leslie; Hayashi, Shim-mo
Abstract: Quercetin and its glycosides possess potential benefits to human health. Several flavonols are available to consumers as dietary supplements, promoted as anti-oxidants; however, incorporation of natural quercetin glycosides into food and beverage products has been limited by poor miscibility in water. Enzymatic conjugation of multiple glucose moieties to isoquercitrin to produce alpha -glycosyl isoquercitrin (AGIQ) enhances solubility and bioavailability. AGIQ is used in Japan as a food additive and has been granted generally recognized as safe (GRAS) status. However, although substantial genotoxicity data exist for quercetin, there is very little available data for AGIQ and isoquercitrin. To support expanded global marketing of food products containing AGIQ, comprehensive testing of genotoxic potential of AGIQ and isoquercitrin was conducted according to current regulatory test guidelines. Both chemicals tested positive in bacterial reverse mutation assays, and exposure to isoquercitrin resulted in chromosomal aberrations in CHO-WBL cells. All other in vitro mammalian micronucleus and chromosomal aberration assays, micronucleus and comet assays in male and female B6C3F1 mice and Sprague Dawley rats, and Muta™ Mouse mutation assays evaluating multiple potential target tissues, were negative for both chemicals. These results supplement existing toxicity data to further support the safe use of AGIQ in food and beverage products. Highlights: α-Glycosyl isoquercitrin (AGIQ) and isoquercitrin were evaluated for genotoxicity. Both chemicals were positive in Ames assays. Isoquercitrin, but not AGIQ, produced chromosomal aberrations in CHO-WBL cells. In vitro and in vivo micronucleus, comet, and Muta™ Mouse assays were negative. Results of GLP studies support the safe use of AGIQ in food and beverage products.